Anti‐N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis is associated with IRF7, BANK1 and TBX21 polymorphisms in two populations. (10th November 2020) - Shu, Y.; Guo, J.; Ma, X.; Yan, Y.; Wang, Y.; Chen, C.; Sun, X.; Wang, H.; Yin, J.; Long, Y.; Yan, X.; Lu, Z.; et al.
Abstract : Background and purpose: Autoantibodies targeting the GluN1(NR1) subunit of the anti‐ N ‐methyl‐D‐aspartate receptor (NMDAR) cause encephalitis. Although it has been shown that anti‐NMDAR encephalitis is associated with human leukocyte antigen (HLA) loci, susceptibility genes for the disease outside the HLA loci remain unidentified. In this study, we aimed to explore the association of anti‐NMDAR encephalitis with non‐HLA genes. Methods: Two Chinese anti‐NMDAR encephalitis cohorts from Han populations were recruited for this study. The North Chinese case–control set consisted of 98 patients and 460 controls, while the South Chinese case–control set included 78 patients and 541 controls. All participants were genotyped for 28 single nucleotide polymorphisms that are associated with autoimmune disorders or infectious diseases. Results: In two independent case–control sets, we identified significant associations of anti‐NMDAR encephalitis with IRF7 rs1131665 (odds ratio [OR] 3.34, 95% confidence interval [CI] 1.99–5.63; P < 0.000001, P adjusted = 0.00004), BANK1 rs4522865 (OR 1.44, 95% CI 1.15–1.82; P = 0.0017, P adjusted = 0.0149), and TBX21 rs17244587 (OR 2.03, 95% CI 1.35–3.05; P = 0.00051, P adjusted = 0.0066). Furthermore, analysis of the three polymorphisms with clinical features of the disease revealed that the IRF7 rs1131665 was associated with tumor status. Conclusion: The present study has for the first time identified non‐HLA susceptibility genes for anti‐NMDAR encephalitis. The association of IRF7, BANK1 and TBX21 with anti‐NMDAR encephalitis suggests that B‐cell activation, Th1 responses, virus infection and the type I interferon signaling pathway are involved in the pathogenesis of the disease. Abstract : This is the first study reporting non‐HLA susceptibility genes for anti‐NMDAR encephalitis. BANK1, IRF7 and TBX21 polymorphisms were associated with anti‐NMDAR encephalitis. IRF7 rs1131665 was associated with tumor status in anti‐NMDAR encephalitis.